Penggabungan Objek Virtual Dengan Objek Nyata Pada Augmented Reality Untuk Museum Lampung - DEW, ossy; Waluyo, Eko (IIB Darmajaya, 2010)
Information on historic objects in the Museum of Lampung are generally in the form of text that are static and limited. Information on the object as name of the object, as long as objects, useful objects, as well as functions found on museum objects shaped only static text with small font so it looks less informative and interesting. Application of augmented reality technology used to develop an application that is useful as a medium for additional information on the objects in the Museum of Lampung in the form of a virtual text, 3D objects, animations, audio, and video. This application was built using software libraries ARtoolkit to display additional information in the form of a virtual text, 3D objects, and animation. Macromedia Flash Player 8 is used as an additional interface for displaying information in the form of audio and video. This application was given the name ARMULA, which stands for Augmented Reality Museum of Lampung. With this application is expected to make the object more informative and interesting, so as to increase the interest and fascination of the public to the Museum of Lampung. Key words : ARMULA, ARtoolkit, Augmented Reality, Library, Museum LampungÂ